Comparative study between a second derivative transition state search and a first derivative Hamilton-Jacobi minimum energy path. - íñez, Rafael; Díaz, Lenin; Sierraalta, Aníbal; Coll, David (Ciencia, 1970)
A comparative study between two different techniques to evaluate minimum energy paths has been carried out using three simple but representative reactions. Minimum energy paths obtained from a first derivative methodology (CARTE suit program) are similar to those found with an intrinsic reaction coordinate (IRC) methodology starting from geometries characterized by a second derivative methodology. The activation energies obtained from an extrapolated curve of the first derivative minimum reaction paths showed relative errors < 5%with respect to the calculated by second derivative technique (Hessian matrix). Different optimization cycles and image numbers were used in the first derivative methodology to explore how these affect the minimum energy paths. For all the reactions studied, 25 optimization cycles were sufficient to reach a converged minimum reaction path and it was checked that in general, the use of 8 or 16 image numbers do not affect the minimum energy path behavior. We have showed how activation energies obtained from a first derivative Hamilton-Jacobi minimum energy path by a simple interpolation of an adjusted curve are in good agreement with the calculated from a second derivative methodology.